Some sweeteners are tastier than others?! Examining the impact of knowing the type of sweetener on consumers' evaluation of lemonade - Prada, M.; Guedes, D.; Doros, A.; Saraiva, M. (Food Quality and Preference, 2025)
Cues related to a product's composition can influence consumer perceptions of food items. For example, information about the type of sweetener used may affect perceptions of healthfulness, caloric content, and expected taste. This study builds on this topic by examining the effect of consumer awareness of sweetener ingredients on their evaluation of lemonade. Participants (n = 101) tasted five samples of lemonade (prepared with 15 % pure lemon juice), each sweetened with a different ingredient: sugar, honey, agave, stevia, or saccharine. The samples were either labeled (e.g., “lemonade with honey”, experimental condition) or unlabeled (e.g., “lemonade E2W”, control condition). We did not find significant differences between the labeling conditions. However, the type of sweetener had a significant main effect across ratings, including evaluation of taste-related (tastiness, sweetness, sourness), health-related (healthfulness, naturalness, calories), and hedonic/acceptance (liking, intentions of future intake, willingness-to-pay) variables. The analysis of correlations between individual differences and lemonade evaluation provides further insights into how the samples were perceived. Specifically, we found a negative association between age and liking of lemonade with sucrose, stevia, and saccharine. Liking lemonades (in general) was positively associated with a preference for the sucrose and agave samples, whereas the preference for sweeter drinks was associated with a higher preference for the lemonade with saccharine. The findings are discussed regarding the implications for the industry and public health.